Shareholder-driven corporate governance - Anand, Anita Indira (London Oxford University Press, 2020)
"This is a book about the ways in which capital markets have come to be shaped by the ubiquity of sophisticated investors. In particular, the majority of today's investors have the economic might and technical capacity to play a role in the decision-making of the corporations in which they invest. This brings with it a host of benefits, such as better corporate strategy and mechanisms to ameliorate the moral hazard that can exist when the people who bear the risk of corporate activity are different than those who make decisions. It also poses regulatory challenges, and a key element of this book is an examination of the ways in which our thinking about corporations and capital markets must change to reflect the prevalence of sophisticated shareholders"--
What is Shareholder-driven Corporate Governance? -- SCG and Corporate Law Theory -- Shareholder Democracy and Shareholder Activism -- Activism, Wolf Packs, and SCG -- Multiple Voting Share Structures -- Shareholders and Takeover Bids : Revisiting the Poison Pill -- Policy Choices and conclusions.
Includes bibliographical references and index.
Keywords: Corporate governance -- Law and legislation; Stockholders -- Legal status, laws, etc